EVALUATION OF THE ANTI-INFLAMMATORY CAPACITY OF BETA-SITOSTEROL IN RODENT ASSAYS - Paniagua-Pérez, Rogelio; Flores-Mondragón, Gabriela; Reyes-Legorreta, Celia; Herrera-López, Brígida; Cervantes-Hernández, Isabel; Madrigal-Santillán, Osiris; Morales-González, José Antonio; Alvarez-González, Isela; Madrigal-Bujaidar, Eduardo (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Beta-sitosterol (BS) is a compound discovered to be present in numerous plants. A number of interestingbiomedical properties have been attributed to BS, including immuno-modulating and anti-inflammatory activities.Therefore, the aim of this report was to evaluate its anti-inflammatory capacity by applying various rodentexperimental tests.Methods. To carry out the objective of the study we applied the methods indicated here. Two of the adopted methodswere based on the passive reverse Arthus reaction: the rat paw edema test and the rat pleurisy assay. We also appliedtwo methods related with the non-specific acute inflammation: the mouse ear edema test, and the mousemieloperoxidase activity assay.Results. The results obtained in all tests established a significant anti-inflammatory potential of BS. In the rat pawedema test we found an inhibitory effect which goes from 50-70%; in the rat pleurisy assay our findings with respect tothe volume of pleural exuded showed a reduction of 46%, as well as a 20% low amount of neutrophils in comparisonwith the level of the control group. In the mouse ear edema test we found a mean inflammatory inhibition of 75%, andwith respect to mieloproxidase activity the results showed a significant inhibition induced by the three doses of BS.Conclusions. In the present study we determined a potent anti-inflammatory capacity of BS in specific and nonspecifictypes of acute inflammation in rodents.